Students teaching students: Can medical students play a part in undergraduate physiology teaching? - Atukorala, Kushani; Silva, Nalinda; Wickramasinghe, Sumudu; Wimalasekera, Savithri (Journal of Bangladesh Society of Physiologist, 2021)
Over the past decade active and self-directed learning has been given precedence in medical curricula. At the Faculty of Medical Sciences, University of Sri Jayewardenepura, Sri Lanka, a novel approach was trialed to teach applied physiology using a student-seminar, where the teaching content was developed by the medical students. Clinically relevant physiology topics were randomly allocated to ten studentgroups. Each group had to deliver their findings to peers and academic tutors during a seminar, using audiovisual aids. This study aimed to explore student perceptions regarding this novel learning experiment. Student perceptions of the seminar were explored using self-administered surveys and were rated. Analysis of subject-related knowledge showed that marks of the participants (n=125) had increased significantly, on average by 13% (t110= -8.878 p<0.001). Majority of students didn’t perceive the student seminar as satisfactory for teaching Applied Physiology. However, student seminars seem to be a useful way to enhance group learning and active self-directed learning. J Bngladesh Soc Physiol 2021;16(1): 57-60